The Protective and Therapeutic Function of Small Heat Shock Proteins in Neurological Diseases - Brownell, Sara E.; Becker, Rachel; Steinman, Lawrence (Frontiers in Immunology, 2012)
Historically, small heat shock proteins (sHSPs) have been extensively studied in the context of being intracellular molecular chaperones. However, recent studies looking at the role of sHSPs in neurological diseases have demonstrated a near universal upregulation of certain sHSPs in damaged and diseased brains. Initially, it was thought that sHSPs are pathological in these disease states because they are found in the areas of damage. However, transgenic overexpression and exogenous administration of sHSPs in various experimental disease paradigms have shown just the contrary – that sHSPs are protective, not pathological. This review examines sHSPs in neurological diseases and highlights the potential for using these neuroprotective sHSPs as novel therapeutics. It first addresses the endogenous expression of sHSPs in a variety of neurological disorders. Although many studies have examined the expression of sHSPs in neurological diseases, there are no review articles summarizing these data. Furthermore, it focuses on recent studies that have investigated the therapeutic potential of sHSPs for neurological diseases. Finally, it will explain what we think is the function of endogenous sHSPs in neurological diseases.